PERANCANGAN APLIKASI SISTEM PAKAR DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR UNTUK MENENTUKAN JENIS GANGGUAN DISLEKSIA BERBASIS WEB - Fakhrul Rahman (Politeknik Meta Industri, 2017)
Dyslexia is a learning difficulty that is best known. Lack of parental supervision to diagnose early reading skills of children caused by factors parents who are too busy and less know the normal development of children. Their services in the form of web-based expert system aims to determine the type of disorder dyslexia as well as to facilitate parents in early diagnosing dyslexia types of disorders experienced by children. The method used to make the application of expert systems is the method of Certainty Factor (CF) is a method to verify whether or not the fact it was definitely uncertain. It is hoped this method will produce an expert system with a degree of certainty that is accurate and suitable to determine something that is uncertain.